LOCAL EXPERIMENTAL NETWORK IS A PREREQUISITE OF SUCCESSFUL BREEDING AND SEED PRODUTION - S. M. Sirota (Овощи России, 2015)
The success in the development of the Institute is associated with seed production and marketing of vegetable varieties of VNIISSOK’s breeding. The affiliated organization, the North-Caucasian experimental station is a structural subdivision of the All- Russian research institute of vegetable breeding and seed production. The stuff of this experimental station work on the problem of seed production of onion, root, cucurbitaceae and leguminous crops in condition of the North-Caucasus.